Pengembangan User Interface Aplikasi Berbasis Mobile dengan Pendekatan User-Centered Design Untuk Meningkatkan Kegunaan dan Pengalaman Pengguna - Sindi Mawarni, Sindi Mawarni; Mahyuni Nur Salina Harahap; Syahanifah Alma; Andira Bayu Oktaviara; M. Khalil Gibran (Jurnal Publikasi Ilmu Komputer dan Multimedia, 2026)
The swift advancement of mobile technology compels developers to create user interfaces (UI) that are both practical and user-friendly. This research focuses on creating a mobile application User Interface through the User-Centered Design (UCD) method, emphasizing users as the core of the complete design process. The approach comprises four UCD phases: analyzing usage context, identifying user needs, developing design solutions, and evaluating through usability testing. Testing involved 30 participants utilizing the System Usability Scale (SUS) approach and think-aloud technique. The findings indicated that the created UI design attained an average SUS score of 82.5 (Excellent category), alongside a 67% enhancement in task efficiency relative to the original design. This research demonstrates that the UCD method greatly improves the usability quality and user experience (UX) of mobile apps.